P-Phenylenediamine induces immediate contact allergy and non-histaminergic itch via MRGPRX2. (5th January 2022) - Che, Delu; Gao, Jiapan; Du, Xueshan; Zheng, Yi; Hou, Yajing; Peng, Bin; Jia, Tao; Geng, Songmei; He, Langchong
Abstract: p -phenylenediamine (PPD) is a common component of hair dye known to induce immediate allergy, even acute dermatitis and contact dermatitis. MAS-related G protein coupled receptor-X2 (MRGPRX2) in mast cells (MCs) mediates small molecular substances-induced pseudo-allergic reactions. However, the role of MRGPRX2 in PPD-induced immediate contact allergy needs further exploration. The aim of this study was to investigate whether PPD activates MCs via MRGPRX2 and induces immediate allergies that contribute to contact dermatitis. Wild-type (WT) and kit w-sh/w-sh mice (MUT) were treated with PPD to observe local inflammation and MC degranulation in vivo . The release of inflammatory mediators was measured in vitro . Histamine 1 receptor (H1 R) −/− mice were used to analyze itch type. PPD caused immediate contact allergy in WT mice, induced scratching, and local inflammatory reactions, while exhibiting minimal effects on MUT mice. PPD did not induce histamine release, but induced significant tryptase release in vivo and in vitro . PPD activated MRGPRX2 to induce MC degranulation in vitro . PPD caused immediate contact allergy in WT mice, induced scratching and local inflammatory reactions, while exhibited minimal effect on MUT mice. PPD did not induce histamine release, while induced significant tryptase release in vivo and in vitro . PPD induced immediate contact allergy by MCs activation via MRGPRX2 and lead to tryptase release. The scratching times showed no significant difference in WT mice or H1 R −/- mice, which indicated PPD caused non-histaminergic itch. The results showed that PPD activated MCs via MRGPRX2 and induced immediate contact allergy, leading to the release of tryptase without monoamine release, which might induce non-histaminergic itch. Graphical abstract: Image 1 Highlights: PPD triggered contact allergy. Mast cells mediated PPD-induced contact allergy in mice. MRGPRX2 mediated PPD-induced human mast cells activation. PPD caused non-histaminergic itch.